Aksiologi : tolak ukur etik dan moral dalam penelitian, penggalian, serta penerapan ilmu - Hapsari, Laura Yesica julya; Faisol, Faisol (Maliki Interdisciplinary Journal, 2025)
Axiology as a branch of philosophy of science plays an important role in providing value direction to scientific activities. This article discusses how axiology becomes an ethical and moral benchmark in the process of research, excavation, and application of science. In a modern world full of technological and information advancements, science is not enough to be judged only in terms of truth and accuracy, but also in terms of social benefits and moral responsibility. Values such as honesty, integrity, justice, and responsibility must be integrated in every scientific stage so that science is not misused and still makes a positive contribution to life. Through an axiological approach, science can be directed to achieve goals that are in line with human values, ethics and sustainability. Thus, axiology becomes an important foundation in shaping a responsible and dignified academic culture.